Relationship between split-step timing and leg stiffness in world-class tennis players when returning fast serves. Issue 17 (2nd September 2019) - Mecheri, Sami; Laffaye, Guillaume; Triolet, Céline; Leroy, David; Dicks, Matt; Choukou, Mohamed A.; Benguigui, Nicolas
ABSTRACT: This study investigated split-step timing when returning serves and whether this timing is related to neuromechanical capabilities in world-class tennis players. In Experiment 1, the split-step timing of four groups of world-class players (male and female ATP/WTA seniors, and ITF juniors) was measured on court when returning serves of the same level players. The four groups initiated the split-step at a similar time, starting around the time ball-racket contact in the serve stroke and landed when early ball-flight information was available. In Experiment 2, the neuromechanical capabilities (leg stiffness and vertical jump performance) of a group of world-class players and three groups of less-skilled tennis players were examined. The results showed an increase in leg stiffness with an increase in the level of expertise. A cross-experiment analysis in world-class male players (ATP/ITF, n = 10) revealed that the timing of initial foot movement was significantly correlated with the leg stiffness (r 2 = 0.54), with later lateral step after the serve in the players who had higher stiffness. The findings support the hypothesis that world-class tennis players adapt perceptual-motor control on the basis of their neuromechanical capabilities and maximise the time before initiating their interceptive action to rely on more reliable information.